Metal-free regioselective cross dehydrogenative coupling of cyclic ethers and aryl carbonyls - Mane, Kishor D.; Mukherjee, Anagh; Vanka, Kumar; Suryavanshi, Gurunath (Journal of Organic Chemistry, 2019)
A highly regioselective, efficient, and metal-free oxidative cross dehydrogenative coupling (CDC) of aryl carbonyls with cyclic ethers has been developed. This method offers easy access to substituted alpha-arylated cyclic ethers with a high functional group tolerance in good to excellent yields. The regioselectivity of this CDC reaction was confirmed by density functional theory (DFT)-based calculations.

Visible light mediated, metal and oxidant free highly efficient cross dehydrogenative coupling (CDC) reaction between quinoxalin-2(1H)-ones and ethers - Mane, Kishor D.; Kamble, Rohit B.; Suryavanshi, Gurunath (New Journal of Chemistry, 2019)
The efficient and metal free, white light mediated 3C alkylation of quinoxalin-2(1H)-ones via a cross dehydrogenative coupling reaction with cyclic ethers using eosin Y as a photocatalyst is described. This reaction has broad substrate scope and strong functional group tolerance with good to excellent yields.

Ti-superoxide catalyzed oxidative amidation of aldehydes with saccharin as nitrogen source: synthesis of primary amides - Kamble, Rohit B.; Mane, Kishor D.; Rupanawar, Bapurao D.; Korekar, Pranjal; Sudalai, A.; Suryavanshi, Gurunath (RSC Advances, 2020)
A new heterogeneous catalytic system (Ti-superoxide/saccharin/TBHP) has been developed that efficiently catalyzes oxidative amidation of aldehydes to produce various primary amides. The protocol employs saccharin as amine source and was found to tolerate a wide range of substrates with different functional groups. Moderate to excellent yields, catalyst reusability and operational simplicity are the main highlights. A possible mechanism and the role of the catalyst in oxidative amidation have also been discussed.

Short enantioselective total synthesis of (+)-tofacitinib - Mane, Kishor D.; Kamble, Rohit B.; Suryavanshi, Gurunath (Tetrahedron Letters, 2021)
An enantioselective total synthesis of Tofacitinib (CP-690,550), a Janus tyrosine kinase (JAK3) specific inhibitor has been achieved from the readily available 4-piperidone. Proline catalysed hydroxylation is the key step for the synthesis of enantiopure 1-benzyl-4-methylpiperidin-3-ol. (C) 2021 Elsevier Ltd. All rights reserved.
Keywords: aminohydroxylation; Hydrogenation; L-proline; piperidone

Acetic acid-catalyzed regioselective C(sp(2))-H bond functionalization of indolizines: concomitant involvement of synthetic and theoretical studies - Mane, Kishor D.; Mukherjee, Anirban; Das, Gourab Kanti; Suryavanshi, Gurunath (Journal of Organic Chemistry, 2022)
An atom economical and environmentally benign protocol has been developed for the regioselective C(sp2)-H bondfunctionalization of indolizines. The acetic acid-catalyzed cross-coupling reaction proceeds under metal-free conditions, producing awide range of synthetically useful indolizine derivatives. The present protocol showed good functional group tolerance and broadsubstrate scope in good to excellent yields. Quantum mechanical investigation using density functional theory (DFT) has played acrucial role in understanding that acetic acid is the key player in determining the actual pathway as the catalyst and its ultrafastnature. Different pathways involving inter- and intramolecular proton transfer, with or without acetic acid, were investigated.Calculated results revealed that a proton shuttle mechanism is involved for the least energetic, most favorable acetic acid-catalyzedpathway. Furthermore, regioselectivity has also been explained theoretically.

Hypervalent-iodine-mediated oxidation followed by the acetoxylation/tosylation of alpha-substituted benzylamines to obtain alpha-acyloxy/tosyloxy ketones - Rupanawar, Bapurao D.; Mane, Kishor D.; Suryavanshi, Gurunath (New Journal of Chemistry, 2022)
An efficient and metal-free method has been developed for the sequential oxidation of alpha-alkylbenzylamines followed by acetoxylation or tosylation for the synthesis of alpha-acyloxy/tosyloxy ketones using hypervalent iodine(iii). The employment of a simple starting material, broad substrate scope and operational simplicity are the key features of this protocol.

Metal-free access to hindered N-alkyl sulfoximines via in-situ generated Aza-oxyallyl cations from functionalized alkyl bromide - More, Satish G.; Mane, Kishor D.; Suryavanshi, Gurunath (Asian Journal of Organic Chemistry, 2022)
Herein, we report a catalyst-free and mild synthetic method for the construction of hindered N-alkyl sulfoximines derivative. A wide range of hindered di-alkyl sulfoximines can be readily obtained from the reaction of alpha-bromo-hydroxamates with a variety of sulfoximines, including diaryl, aryl-alkyl, di-alkyl and heteroaryl sulfoximines.
Keywords: alpha-Bromo hydroxamates; Aza-oxyallyl cations; Di-alkyl sulfoximines; metal-free; Sulfoximines

Regioselectivity in metalloradical catalyzed C-H bond activation: a theoretical study - Mukherjee, Anirban; Singh, Ritesh; Mane, Kishor D.; Das, Gourab Kanti (Journal of Organometallic Chemistry, 2022)
Pure quantum mechanical calculations were performed to find out the origin of regioselectivity under the metalloradical catalysis (MRC) by Co(II)-porphyrin, which showed regioselectivity is the inherent property of the aminyl radical generated from the sulfamoyl azide substrate. Different conformational analysis for the transition state from alpha-Co-III-aminyl radical to zeta-Co-III-alkyl radical formation have been studied to find out the most stable conformation for the preferable selectivity. The outcome of our study completely agrees with the reported experimental results. (C) 2021 Elsevier B.V. All rights reserved.
Keywords: C-H activation; DFT; Metalloporphyrin; Metalloradical; Regioselectivity

Visible light-promoted, photocatalyst-free C(sp(2))-H bond functionalization of indolizines via EDA complexes - Mane, Kishor D.; Rupanawar, Bapurao D.; Suryavanshi, Gurunath (European Journal of Organic Chemistry, 2022)
The catalyst and additive-free, photo-driven cross dehydrogenative coupling (CDC) reaction initiated by electron donor-acceptor (EDA) complexes between electron rich indolizines and electron poor quinones has been demonstrated. This green transformation reveals the advantages of operational simplicity, mild reaction conditions and good functional group tolerances.
Keywords: Blue LED; CDC; EDA; Indolizine; Quinone

Synthesis of 3 alkyl and 1,3-Bis(alkyl)indolizine amides from a-bromohydroxamates - Mane, Kishor D.; Bagwe, Sagar S.; More, Satish G.; Suryavanshi, Gurunath (Tetrahedron Letters, 2023)
A simple and catalyst-free method has been developed for the synthesis of hindered indolizine amide derivatives from functionalized alkyl bromides. The reaction of a variety of indolizine derivatives with azaoxyallyl cations generated in situ from a-bromoamides afforded a wide range of synthetically important mono- and di-alkylated indolizine amide derivatives in good to excellent yields.@2023 Elsevier Ltd. All rights reserved.
Keywords: a -Bromohydroxamates; Amides; HFIP; Indolizine